Pluralidade cultural e educação física: elaboração de material didático - Ferreira, Aline Fernanda [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
In 1997, the National Curriculum Parameters (BRASIL, 1997a) proposed the incorporation of the Transversal Themes in all of the knowledge areas. Specifically in the School Physical Education, the teacher working with transversality must stabilish bridges between the body culture practice with these themes. Promote this relationship is not a simple task and there are many problems that stuck the advance of this propose. So, thinking about making didactical formulat teaching stragies and think about the development of their practice. Another challenge is considerate as a beginning in the pedagogic activity the student’s knowledge and experience, as listening during the process of knowledge construction. In this way, the aim of this research is investigate the 8th and 9th grade of the primary school students conception about Cultural Plurality. After this, using the information taken gron the students, we are going to present subisidies to make a textbook, for the teachers and for students, with Physical Education activities possibilies with this Transversal Theme. Keeping in mind the aim of this research, we used the semi-structed interview as a instrument of data collection. The interview was made with 30 students of the 8th and 9th grade the primary school from two statual schools of Rio Claro city. The procediments were executed following the ethics comite requirements. In other to associate the Cultural Plurality with Physical Education, dance and physical adventure activities contents were selected. The results showed that the students know few thinks about this Transversal Themes, because they had apoor knowledge, according to National Curriculum Parameters. In scholar environment and Physical Education classes, there are many cases of prejudice and discrimination, mostly by the leack of ability. Nonetheless, most of the students are able to...(Complete abstract click electronic access below)

Em 1997, os Parâmetros Curriculares Nacionais (PCNs/BRASIL, 1997) propuseram a incorporação dos Temas Transversais em todas as áreas do conhecimento. Especificamente na Educação Física, o professor ao trabalhar com a transversalidade deve estabelecer pontes entre as práticas da cultura corporal com tais temas. Promover esta relação não é tarefa simples e são muitos os empecilhos que limitam o avanço desta proposta. Assim, pensar em elaborar livros didáticos se torna necessário para oferecer apoio aos professores a formularem estratégias de ensino e refletirem sobre o desenvolvimento de suas práticas. Outro desafio é considerar como princípio na atividade pedagógica os conhecimentos e experiências dos alunos, bem como ouvi-los durante o processo de construção do conhecimento. Nesse sentido, o objetivo do presente estudo é primeiramente investigar a concepção dos alunos do 8º e 9º ano do Ensino Fundamental sobre a Pluralidade Cultural. E num segundo momento, por meio das informações obtidas destes alunos, apresentar subsídios para a construção de um livro didático, tanto para o professor quanto para o aluno, com possibilidades de trabalho da Educação Física com este Tema Transversal. Tendo em vista o objetivo do estudo, utilizou-se a entrevista semi-estruturada como instrumento para coleta de dados. A entrevista foi realizada com 30 alunos do 8° e 9° ano do Ensino Fundamental de duas escolas estaduais do município de Rio Claro. Os procedimentos foram executados tendo em vista as exigências do comitê de ética. Para associar estas temáticas da Pluralidade Cultural com a Educação Física, selecionou-se os conteúdos de dança e atividades físicas de aventura (AFA). Os resultados destacaram que os alunos conhecem pouco sobre este Tema Transversal, pois tiveram conteúdo aquém do estabelecido pelos PCNs. No ambiente...(Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Material didático; Esportes radicais; Dança na educação física; Educação física - Estudo e ensino; Teaching - Aids and devices; Radical sports; Physical education and training - Study and teaching